Los títeres para estimular el ámbito relaciones lógico – matemáticas en los niños de inicial II de la escuela Mons. Juan María Riofrío, de la ciudad de Loja, período 2018 – 2019. - Bermeo Tene, Irma Lucia (2019)
This research work: THE PUPPETS TO STIMULATE THE AREA OF LOGICAL - MATHEMATICAL RELATIONS, IN THE CHILDREN OF INITIAL II OF THE MONS SCHOOL. JUAN MARÍA RIOFRIO, OF THE CITY OF LOJA, PERIOD 2018 - 2019. Its General Objective: Describe the use of titles to promote the field of logical - mathematical relations; The methods used for the research were inductive, deductive, analytical-synthetic, statistical. The instruments and techniques applied were the interview directed to the teacher, the formal qualitative report that specifies knowing the degree of development of the skills of the field of logical relations - mathematics, where it is evidenced that 16 children corresponding to 79% have not acquired Even the knowledge. In the teacher interview it was verified that she knows the puppets and their use, however, not the United States to deal with the aforementioned field. The elaboration and application of the alternative proposal with the purpose of solving the problem encountered, constant of a guide of activities with titles that favor in a fun and fun way in the development of the skills of the field logical-mathematical relations. Therefore, it is recommended that teachers of the initial level continue using the activities with degrees, which is considered in an educational and recreational way in the development of the field of mathematical logical relations, since it is essential for the integral development of children .